A decades-long investigation of acute metabolism-based hepatotoxicity by herbal constituents: a case study of pennyroyal oil. (16th December 2014) - Gordon, Perry; Khojasteh, S. Cyrus
Abstract: Herbal supplements are often regarded as "natural", and are, therefore, considered by many to be safer than pharmaceuticals; however, the adverse effects of these supplements are under-reported in many cases. Many herbal supplements, such as pyrrolizidine alkaloids, kava, chaparral and germander, are known to induce liver injury, which, in general, is one of the main toxicity liabilities observed in the clinic and accounts for about half of total liver failures. One example is the hepatotoxicity of pennyroyal oil, which is ingested as an abortifacient, among other uses. For three decades, the late Professor Sidney Nelson contributed to our understanding of the mechanism of toxicity of pennyroyal and broadened our understanding of chemical toxicology. Here we present the studies and review the findings on acute hepatotoxicity of pennyroyal oil. These studies involved the isolation and characterization of pennyroyal components, determination of the appropriate animal models, identification of the structural requirement for toxicity and determination of the target enzymes and the enzymes involved in the process of bioactivation. Studies with stable isotope labeled pennyroyal metabolites, pulegone and menthofuran, furthered our understanding of the role of cytochrome P450 in the oxidation of these compounds. This review presents the investigational tools used in the study of pennyroyal oil, allowing the reader to not only appreciate these methods but also utilize them to tackle and better understand metabolism-based toxicity in their own projects.